The Role of Social Media in Transforming Learning at Higher Education Institutions During the Pandemic: PLS-SEM Approach - Al-Tahitah A.; Al-Momani A.; Al-Sharafi M.A.; Abdulrab M.; Hajar M.A. (Springer Science and Business Media Deutschland GmbH, 2025)
This study explores how university students across various Malaysian institutions have embraced social media for learning purposes amidst the COVID-19 pandemic. A comprehensive online survey, administered to 549 participants, focuses on constructs of the HBM and TBP, perceived susceptibility, perceived severity, perceived barriers, health motivation, perceived benefits, self-efficacy, perceived behavioural control, subjective norms, as well as attitude, and behavioural intention. Following meticulous data analysis utilizing partial least squares structural equation modeling, the study verifies the reliability and validity of the measurement model. The findings indicate that perceived severity, perceived barriers, perceived benefits, self-efficacy, perceived behavioral control, and subjective norms exert significant influence on students? attitudes, thereby molding their behavioral intentions. This underscores the pivotal role of these factors in shaping students? perspectives and intentions, providing valuable insights for educators and policymakers. While perceived susceptibility and health motivation exhibit limited impact, the proposed model explains a substantial proportion of the variance in attitude and behavioural intention. This study underscores the nuanced dynamics of social media adoption in the educational context and provides insights valuable for educators and policymakers navigating the challenges posed by the global pandemic. ? The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.